Mo content-depended competition between Cr2O3 enrichment and selective dissolution of CoCrFeNiMo x high entropy alloys - Qian Hu; Cheng-Ping Ye; Shang-Chen Zhang; Xian-Zong Wang; Cheng-Feng Du; Haifeng Wang (npj Materials Degradation, 2022)
Abstract The corrosion and passivation behavior of the as-cast CoCrFeNiMo x (x = 0, 0.2, 0.4, 0.6, 0.8, and 1.0) high entropy alloys (HEAs) are investigated. With the addition of Mo, increasing Mo and Cr riched σ phase precipitates from the primary FCC phase. The corrosion resistance of the CoCrFeNiMo x HEAs strongly depends on the phase structure and the passive film. Generally, Mo promotes the selective dissolution of the FCC phase and the enrichment of Cr2O3 in the passive film, the former deteriorates the corrosion resistance while the latter enhances it. Interestingly, the hypoeutectic Mo0.6 exhibits a higher corrosion resistance than that of Mo0.4, eutectic Mo0.8, and hypereutectic Mo1. Analysis of surface passive film and the composition of alloy phases implies that the Cr2O3 enrichment dominates in Mo0.6 while selective dissolution governs in Mo x (x = 0.4, 0.8, and 1.0). Mo content-depended competition between the Cr2O3 enrichment and selective dissolution is discussed.